Holistic Approaches During Pregnancy and Their Implications for Midwifery Practice - Ellyzabeth Sukmawati; Titi Alfiani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This literature review explores holistic approaches during pregnancy and their implications for midwifery practice. Holistic care addresses physical, psychological, social, and spiritual dimensions of maternal health, aiming to promote overall well-being and positive pregnancy outcomes. By synthesizing evidence from studies published between 2020 and 2025, this review highlights the benefits of integrating holistic methods such as stress reduction techniques, nutritional support, psychosocial counseling, and culturally sensitive care within midwifery. The findings suggest that holistic care enhances emotional resilience, reduces anxiety and depression, and strengthens the mother infant bond. However, challenges remain in standardizing holistic practices, ensuring adequate training for midwives, and overcoming systemic barriers. The review underscores the need for midwives to adopt a comprehensive, woman centered approach supported by ongoing education and interdisciplinary collaboration. Future research should focus on evaluating holistic interventions’ effectiveness and developing scalable models to improve maternal and neonatal outcomes globally. Ultimately, holistic pregnancy care offers a promising framework to enrich midwifery practice and support maternal well-being throughout pregnancy.